Radiolabeling of functional oligonucleotides for molecular imaging - Liu, Dunfang; Xia, Qian; Ding, Ding; Tan, Weihong (Frontiers in Bioengineering and Biotechnology, 2022)
Molecular imaging has greatly advanced basic biology and translational medicine through visualization and quantification of molecular events in a cellular context and living organisms. Nuclear medicine, including positron emission tomography (PET) and single-photon emission tomography (SPECT), is one of the most representative molecular imaging modalities which is widely used in clinical theranostics. Recently, numerous molecular imaging agents have been developed to improve the quality and expand the applicable diseases of molecular imaging. Based on the choice of specific imaging agents, molecular imaging is capable of studying tumor biological activities, detecting tumor metastasis, and imaging Alzheimer’s disease-related amyloid proteins. Among these imaging agents, functional oligonucleotides-based imaging probes are becoming increasingly important due to their unique features. Antisense oligonucleotides, small interfering RNA, and aptamers are privileged molecular tools in precision medicine for cancer diagnosis and treatment. These chemically synthesized oligonucleotides without batch-to-batch variations are flexible to incorporate with other molecules without affecting their functionalities. Therefore, through the combination of oligonucleotides with radioisotopes, a series of molecular imaging agents were developed in the past decades to achieve highly sensitive and accurate biomedical imaging modalities for clinical theranostic. Due to the nature of oligonucleotides, the strategies of oligonucleotide radiolabeling are different from conventional small molecular tracers, and the radiolabeling strategy with rational design is highly correlated to the imaging quality. In this review, we summarize recent advancements in functional oligonucleotide radiolabeling strategies and respective molecular imaging applications. Meanwhile, challenges and future development insights of functional oligonucleotide-based radiopharmaceuticals are discussed in the end.